Inhibitory properties of a latent inhibitor after its compound preexposure with several novel stimuli: evidence from human conditioning - Liberal, Unai; Rodríguez, Gabriel; Nogueiras, Paula; Nelson, James Byron; Hall, Geoffrey (Frontiers in Psychology, 2025)
Latent inhibition refers to the retardation in learning an association between a target stimulus and an outcome when the target stimulus has been pre-exposed in the absence of consequences. The inhibitory properties of latent inhibitors have been the subject of controversy, as standard latent inhibition training—consisting of pre-exposure to the target stimulus alone—does not provide the latent inhibitor with the ability to pass a summation test, a key criterion for demonstrating genuine inhibition. However, previous research with animals has shown that a specific pre-exposure procedure, in which the target stimulus (A) is presented in compound with successive novel stimuli (An1, An2, An3…), can endow the target with sufficient inhibitory properties to pass both retardation and summation tests. To examine whether this phenomenon generalizes to humans, we conducted two experiments using a video game-based conditioning paradigm. Experiment 1 demonstrated that this compound pre-exposure schedule enhanced the retardation effect compared to standard pre-exposure or control conditions. Experiment 2 revealed that the target stimulus pre-exposed with novel stimuli significantly reduced responding when tested in compound with an excitatory conditioned stimulus, thus passing the summation test. These results suggest that compound pre-exposure facilitates the acquisition of inhibitory properties in humans, consistent with findings from animal studies. The findings are discussed within the framework of Hall-Rodríguez model, emphasizing the role of expectancy violation during pre-exposure in strengthening inhibitory associations. Implications for clinical applications, particularly in enhancing exposure therapy for anxiety disorders, are also considered.